Implementasi manajemen risiko terhadap perlindungan data nasabah pada proses digitalisas perbankan syariah - Royani, Nindy Dwi (Maliki Interdisciplinary Journal, 2024)
The rapid advancement of technology supports the digitalization process in Islamic banking in Indonesia. This can be seen with the integration of information technology in operational and service activities in Islamic banking. However, in the process of digitalization of Islamic banking there are operational risks in the form of cybercrime such as fraud and data leakage. This study aims to analyze how the implementation of risk management on customer data protection in the process of digitalization of Islamic banking. The method used in the research is the literature study method with a descriptive approach. The data source is secondary data obtained from the Google Scholars website with the theme of risk management. The data analysis tools used are Microsoft Excel and Mendeley Dekstop software. The results showed that the implementation of risk management in the Islamic banking digitalization process can support the success of the Islamic banking digitalization process in Indonesia. The implementation of risk management in Islamic banking is a series of processes and methods used in managing risks by identifying risks, measuring operational risks through the application of Risk Control Self Assessment, monitoring risks, and controlling risks that may occur, as well as mitigating risks.